2016
DOI: 10.3390/plants5030036
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Cruciferin and Napin of Brassica napus (Canola) Show Distinct Responses to Changes in pH and Temperature

Abstract: The two major storage proteins identified in Brassica napus (canola) were isolated and studied for their molecular composition, structural characteristics and the responses of structural features to the changes in pH and temperature. Cruciferin, a complex of six monomers, has a predominantly β-sheet-containing secondary structure. This protein showed low pH unstable tertiary structure, and distinctly different solubility behaviour with pH when intact in the seed cellular matrix. Cruciferin structure unfolds at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 52 publications
17
113
0
Order By: Relevance
“…Native gel electrophoresis affirmed cruciferin solubility reduced with increasing dry heat. Progressive dry heat-induced changes in the structure of cruciferin were similarly reported by Perera et al (2016). Reduced ability to extract protein from MHP meal suggests the formation of irreversible bonds and formation of insoluble high MW protein aggregates in canola meal treated under these conditions.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Native gel electrophoresis affirmed cruciferin solubility reduced with increasing dry heat. Progressive dry heat-induced changes in the structure of cruciferin were similarly reported by Perera et al (2016). Reduced ability to extract protein from MHP meal suggests the formation of irreversible bonds and formation of insoluble high MW protein aggregates in canola meal treated under these conditions.…”
Section: Discussionsupporting
confidence: 58%
“…The AOF (2004) reported darker meal was beneficial quality for dairy; however, Classen et al (2005) reported early reactions causing colour change negatively impact AA digestibility by poultry and thus are unfavourable for monogastric digestion. (Perera et al, 2016) and aggregation (Davis & Williams 1998). Folawiyo and Apenten (1997) reported heat treatment of rapeseed napin induced irreversible changes in So at 90 o C. At 20 to 120 o C and 140 to 180 o C, MHP meal shifted So from low to high relative to control meal, to suggest at low and moderate processing temperatures MHP induces protein folding events promoting surface hydrophilic conformation; however, at 140 to 180 o C modifications of turning of side-chains outwards, commonly associated with protein unfolding, loss of 2 o and 3 o structure, scrambling of disulphide bonds, and formation of irreversible protein aggregates contribute to increases in protein hydrophobicity (Davis & Williams, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the DSC results for BLG at 2% w/w WP and for ALA at the range of 2 -8 % w/w WP are not reported because of uncertainties during identification and peak integration at these low concentrations. The thermal transition point of cruciferin was detected at higher temperatures compared to whey proteins in the expected (Kim, Varankovich, & Nickerson, 2016) range of 87 -96 o C. The second protein fraction present in RP, napin, was not detected due to its reportedly high thermo-stability (Perera, McIntosh, & Wanasundara, 2016). The enthalpy of denaturation of BLG and ALA generally did not vary a lot with protein concentration.…”
Section: Discussionmentioning
confidence: 90%
“…Cruciferin represents 60% of the total protein content of canola seeds. It is a neutral protein (pI = 7-7.5), made of six sub-units with a high molecular weight around 300 kDa 3 . Each monomer is composed of two polypeptide chains (30 and 20 kDa), linked by a disulfide bond.…”
Section: Introductionmentioning
confidence: 99%